(untitled) (Web of Teachers: Inderscience Research, 2025)
This article provides an in-depth analysis of the psychological challenges faced by adolescents due to the growing influence of negative social media content. As digital platforms become central to communication and identity formation, many teenagers experience emotional and mental disturbances. Key psychological effects such as anxiety, depression, low self-esteem, and social isolation often stem from cyberbullying, unrealistic comparisons, and body image pressure. The article further highlights the importance of emotional intelligence, supportive learning environments, and strategic digital literacy education to counter these effects.